Air pollution, pollens, and daily admissions for asthma in London 1987–92. Issue 10 (1st October 1998) - Anderson, H R; de Leon, A Ponce; Bland, J M; Bower, J S; Emberlin, J; Strachan, D P
Abstract : BACKGROUND: A study was undertaken to investigate the relationship between daily hospital admissions for asthma and air pollution in London in 1987–92 and the possible confounding and modifying effects of airborne pollen. METHODS: For all ages together and the age groups 0–14, 15–64 and 65+ years, Poisson regression was used to estimate the relative risk of daily asthma admissions associated with changes in ozone, sulphur dioxide, nitrogen dioxide and particles (black smoke), controlling for time trends, seasonal factors, calendar effects, influenza epidemics, temperature, humidity, and autocorrelation. Independent effects of individual pollutants and interactions with aeroallergens were explored using two pollutant models and models including pollen counts (grass, oak and birch). RESULTS: In all-year analyses ozone was significantly associated with admissions in the 15–64 age group (10 ppb eight hour ozone, 3.93% increase), nitrogen dioxide in the 0–14 and 65+ age groups (10 ppb 24 hour nitrogen dioxide, 1.25% and 2.96%, respectively), sulphur dioxide in the 0–14 age group (10 μg/m 3 24 hour sulphur dioxide, 1.64%), and black smoke in the 65+ age group (10 μg/m 3 black smoke, 5.60%). Significant seasonal differences were observed for ozone in the 0–14 and 15–64 age groups, and in the 0–14 age group there were negative associations with ozone in the cool season. In general, cumulative lags of up to three days tended to show stronger and more significant effects than single day lags. In two-pollutant models these associations were most robust for ozone and least for nitrogen dioxide. There was no evidence that the associations with air pollutants were due to confounding by any of the pollens, and little evidence of an interaction between pollens and pollution except for synergism of sulphur dioxide and grass pollen in children (p<0.01). CONCLUSIONS: Ozone, sulphur dioxide, nitrogen dioxide, and particles were all found to have significant associations with daily hospital admissions for asthma, but there was a lack of consistency across the age groups in the specific pollutant. These associations were not explained by confounding by airborne pollens nor was there convincing evidence that the effects of air pollutants and airborne pollens interact in causing hospital admissions for asthma.